2004
DOI: 10.1103/physreve.70.016402
|View full text |Cite
|
Sign up to set email alerts
|

Beat wave injection of electrons into plasma waves using two interfering laser pulses

Abstract: An electron injector concept that uses a single injection laser pulse colliding with a pump laser pulse in a plasma is analyzed. The pump pulse generates a large amplitude laser wakefield (plasma wave). The counterpropagating injection pulse collides with the pump laser pulse to generate a beat wave with a slow phase velocity. The ponderomotive force of the slow beat wave is responsible for injecting plasma electrons into the wakefield near the back of the pump pulse. Test particle simulations indicate that si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
130
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 22 publications
3
130
1
Order By: Relevance
“…Recent experiments have also shown that acceleration of the electron bunch over long distances resulted in the production of high quality electron bunches with narrowed energy distributions and increased energies, even when controlled injection was not used [11][12][13], and this has also been observed in simulations [11,14,15]. By maintaining the laser intensity over many Z R , controlled guiding can also allow efficient production of a long, high gradient wake structure without self trapping, allowing the use of controlled injection schemes which may produce very high quality beams [16][17][18]. Hence, guiding of relativistically intense pulses is essential to obtaining high energy, low emittance, low energy spread electron beams from high gradient laser wakefield accelerators.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Recent experiments have also shown that acceleration of the electron bunch over long distances resulted in the production of high quality electron bunches with narrowed energy distributions and increased energies, even when controlled injection was not used [11][12][13], and this has also been observed in simulations [11,14,15]. By maintaining the laser intensity over many Z R , controlled guiding can also allow efficient production of a long, high gradient wake structure without self trapping, allowing the use of controlled injection schemes which may produce very high quality beams [16][17][18]. Hence, guiding of relativistically intense pulses is essential to obtaining high energy, low emittance, low energy spread electron beams from high gradient laser wakefield accelerators.…”
mentioning
confidence: 84%
“…Experiments and simulations show that a large plasma wave is driven by the laser pulse. By allowing drive laser pulses to propagate over many Z R in the plasma, the acceleration distance and hence the electron beam energy and quality of plasma based laser accelerators can be dramatically improved [11,14,15], and controlled injection experiments [16][17][18] may be possible.…”
mentioning
confidence: 99%
“…The simulations also indicate that a plasma wave averaging 200-300 GV/m is excited, in the last 0.5 mm of guide length. No electrons are self trapped at 4 TW, making this an attractive structure for controlled injection experiments (Esarey et al 1997;Schroeder et al 1999;Fubiani et al 2004), as will be discussed below. When increasing the laser power up to the 10 TW level, electron beams were produced with unprecedented properties, as discussed in section 2c.…”
Section: (B) Guiding Relativistic Intensities In Plasma Channelsmentioning
confidence: 99%
“…1999; Fubiani et al 2004). Experiments are underway to study laser triggered injection, and are predicted by theory to produce narrow energy spread bunches with greater stability.…”
Section: (C) Future Challengesmentioning
confidence: 99%
“…The uncontrolled nature of the trapping process is believed to contribute to the fluctuations. Experiments are underway to control this trapping and acceleration process at the Naval Research Laboratory using the LIPA method (Laser Ionization Ponderomotive Acceleration) [27], at the University of Michigan using the LILAC method (Laser Injection Laser Acceleration) [28], and at LBNL using the CPI method ( Colliding Pulse Injection) [29,30,31]. Progress on the CPI method is summarized below in Sec.…”
Section: Introductionmentioning
confidence: 99%